GENDER PARTNERSHIP AND TOLERANCE PHENOMENON - R. I. Kuzmenko (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
Purpose. The article analyzes the role of such a phenomenon as tolerance in a partnership between a man and a woman, emphasizing its importance and necessity in their relations. The purpose of the study is to estimate the role of the tolerance phenomenon in the process of gender partnership. Theoretical basis. The works of domestic and foreign scientists contributed to estimate the function of tolerance during communication, cooperation and co-creation. In this paper the methodology of E. Fromm and N. Khamitov’s metaanthropology is used. Originality. It was proved that the success of a gender partnership depends on how tolerant its participants are to each other. Besides this, it has been established that tolerance is the main criterion for gender partnership. The idea of tolerance is considered as the way to fruitful development of human relations. For the first time it has been determined that gender partnership can be manifested on the ordinary, frontier and metafrontier levels of human existence. Tolerance has its own specifics and a manifestation on each of them. Conclusions. Metaanthropology has helped to estimate the role of tolerance among men and women in the partnership process. So, it can be stated that tolerance is a basis for gender partnership that harmonizes the relationship among a man and a woman and makes them egalitarian. Only on the metafrontier level of human being tolerance can be manifestation of individual integrity. Sincere, open interaction and creative work with Other are formed on this foundation. Thus, gender partnership with inexhaustible, complementary potential is the vector of development of human relations.